Find the value of 3x square- 5x + 3 .at x = -2
Answers
Answered by
7
The given equation =
![3 {x}^{2} - 5x + 3 3 {x}^{2} - 5x + 3](https://tex.z-dn.net/?f=3+%7Bx%7D%5E%7B2%7D++-+5x+%2B+3)
since , x = -2
Therefore , it satisfies the equation
![= 3 ( - 2)^{2} - 5( - 2) + 3 = 3 ( - 2)^{2} - 5( - 2) + 3](https://tex.z-dn.net/?f=+%3D+3+%28+-+2%29%5E%7B2%7D++-+5%28+-+2%29+%2B+3)
![= 3 \times 4 + 10 + 3 = 3 \times 4 + 10 + 3](https://tex.z-dn.net/?f=+%3D+3+%5Ctimes+4+%2B+10+%2B+3)
![= 12 + 10 + 3 = 12 + 10 + 3](https://tex.z-dn.net/?f=+%3D+12+%2B+10+%2B+3)
![= 25 = 25](https://tex.z-dn.net/?f=+%3D+25)
since , x = -2
Therefore , it satisfies the equation
Answered by
0
Answer:
=> 25
Step-by-step explanation:
Here it is given that
We have to find the value of the expression.
Given expression:
When
To find:- The value of the expression,
Now, by substituting the value of x as in the expression:
As we have,
=>
=>
Simplifying it further we get,
=> 12 + 10 + 3
=> 25
Hence, the required solution is 25.
Similar questions